ADESÃO À TERAPIA IMUNOSSUPRESSORA EM TRANSPLANTADOS RENAIS - Morais, Regina de Fátima Cruz de (2013)
Introduction: Adherence to immunosuppressive therapy is essential for the maintenance of renal graft, however, non-adherence is a major challenge for effective long-term immunosuppressive. Objectives: To assess adherence to immunosuppressant therapy in renal transplant recipients. Methods: Cross sectional study with a quantitative approach, from May/2012 to abril/2013 with 151 kidney transplant recipients followed up at outpatient posttransplant Renal Transplant Service, University Hospital of the Federal University of Maranhão (HUUFMA). Two instruments were used for data collection. At first, we collected sociodemographic, clinical data and the dispensing of immunosuppressants. The second was the Immosupressive Therapy Adherence Scale -ITAS, to measure adherence by self-report. Adherence to immunosuppressants was assessed by self-report methods, dispensing of immunosuppressants and a combination of self-report and dispensing. At the junction of the variable compliance with the sociodemographic and clinical variables, we applied the Test t for independent samples and the Mann-Whitney for variables without normal. For comparisons of categorical data were used the Chi-Square test. Analyzed the Kappa coefficients to verify the agreement between the methods for evaluating adherence. Considered significant if the p-value below 0.05. Results: Of the 151 transplants, 51.7% were male, 74.8% color/mulatto, 55.7% married, 58.9% were inactive with family income above minimum wage 77.5%, more than 8 years were 62.9% and the average age was 40.33 ± 11, 7 years. Was found a percentage of non-adherence (60.3%) by self-report, (71.5%) by dispensing of immunossuppressive and (37,1%) by combination of by self-report and dispensing of immunossuppressive. Variables that had significant associations with nonadherence were: being transplanted living donor (p = 0.03), younger age (p = 0.04) and the type of immunosuppressive agent used (p = 0.04). higher levels of creatinine were found in the non bonded by self-report (p = 0.04) and membership combined (p = 0.02). Conclusions: poor adherence to immunosuppressive therapy found in this series is an important risk factor for adverse clinical outcomes such as chronic rejection and graft loss.